2014
DOI: 10.1089/lap.2013.0109
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Laparoscopic Percutaneous Extraperitoneal Closure for Inguinal Hernias and Hydroceles in Children: A Comparison with Traditional Open Repair

Abstract: LPEC is safe and effective for inguinal hernias and hydroceles in children, regardless of age, sex, and incarceration and could reduce the incidence of metachronous contralateral hernias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 13 publications
7
23
0
Order By: Relevance
“…Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results [24]. In particular, LPEC, reported by Takehara et al [4], is performed widely in Japan [10,11,[13][14][15]. There have been some comparisons between traditional open herniorrhaphy and laparoscopic repair, including a randomized study and a systematic review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results [24]. In particular, LPEC, reported by Takehara et al [4], is performed widely in Japan [10,11,[13][14][15]. There have been some comparisons between traditional open herniorrhaphy and laparoscopic repair, including a randomized study and a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of laparoscopic hernia repair can be divided into two groups. The first group is intraperitoneal internal ring suturing [1][2][3], and the second is extraperitoneal closure [4][5][6][7][8][9][10][11][12][13][14][15]. Recently, there is a trend for increased reports of extraperitoneal closure because of its ease of use and good results.…”
mentioning
confidence: 99%
“…Although our patient population was relatively small, LPEC may be safe and efficient for treating pediatric hydrocele in the same manner as IH. 9 The rate of long-term complications, such as infertility due to obstruction of the vas deferens, should be compared between these patient groups in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown no increased risk associated with the laparoscopic repair, including overall complications, testicular blood flow, and volumes. 15,23,24 Protection of adjacent or incarcerated structures has also been reported. In a report by Kaya et al, 25 laparoscopy allowed for direct visual control, examination of the incarcerated organ, and repair of the hernia in the same operative time.…”
Section: Current Evidencementioning
confidence: 98%